Ruby on Rails bible - Fisher, Timothy (Timothy R.) (Wiley, 2008)
"Thanks to the explosive growth in popularity of the Rails framework, the equally popular Ruby programming language now has a great place to hang its hat. The powerful combination of the two provides the perfect toolset to create Web applications that feature concise code, clean syntax, and easy maintenance. This book is your best guide on how to jump on the RoR bandwagon, from the basics of Ruby programming to advance techniques for experienced Rails developers."--Jacket